Economic valuation of forest ecosystem services: Methodology and monetary estimates - Aline Chiabai; C. M. Travisi; H. Ding; A. Markandya; P. A. L. D. Nunes (Fondazione Eni Enrico Mattei (FEEM), 2009)
By using ad hoc value transfer protocols, this paper offers a methodological contribution and provides accurate per hectare estimates of the economic value of some selected ecosystem services for all forest biomes in the world, identified following the Millennium Ecosystem Assessment taxonomy MEA. The research also estimates potential total economic losses from policy inaction in year 2050. Final results show that total losses are significant. The total figure is exteuro78 billion, the greatest losses coming from North America and Mexico, followed by Africa, Russia and some Asiatic countries. Most of this loss is attributable to provisioning services and carbon sequestration, while only a minor part is due to loss of cultural services. In terms of biomes the greatest losses are from boreal and warm mixed forests, followed by tropical forests. These results may be surprising to some who argue that it is the loss of tropical forests, particularly the Amazon, that is the most significant. A detailed analysis, shows, however, that this is not the case. The best estimates point to greater losses in areas where use and non-use values are highest, which includes North America.
Keywords: O13; Q23; Q26; Q51; Q54; Q57; 330; Forest; Ecosystem Services; Biodiversity; Valuation; Value Transfer